2020
DOI: 10.1016/j.jjcc.2020.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Trends in long-term prognosis according to left ventricular ejection fraction after acute coronary syndrome

Abstract: Our aim was to investigate trends in prognosis among survivors of acute coronary syndrome according to left ventricular ejection fraction during a 16-year period. Methods: Data were derived from the Acute Coronary Syndrome Israeli Survey during the years 2000-2016. Patients aged 18 years and older were included in the analysis (N = 11,725). Patients were classified into two groups based on their left ventricular ejection fraction: preserved (!50%) and reduced (<50%) and also according to their acute coronary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
2
6
0
1
Order By: Relevance
“…LVEF is a quantitative marker to evaluate cardiac systolic function. previous study showed that patients with preserved left ventricular ejection fraction had lower one and 3-year mortality rates as compared with reduced left ventricular ejection fraction regardless of the acute coronary syndrome period onset (Yahud et al, 2020). Our results showed that GF for therapeutic angiogenesis could increase LVEF by 2.05%.…”
Section: Discussionsupporting
confidence: 57%
“…LVEF is a quantitative marker to evaluate cardiac systolic function. previous study showed that patients with preserved left ventricular ejection fraction had lower one and 3-year mortality rates as compared with reduced left ventricular ejection fraction regardless of the acute coronary syndrome period onset (Yahud et al, 2020). Our results showed that GF for therapeutic angiogenesis could increase LVEF by 2.05%.…”
Section: Discussionsupporting
confidence: 57%
“…LVEF not only reflects the pumping function of the heart but also has predictive value for prognosis [2,3]. In this study, at the follow-up, the LVEF of the patients had significantly increased, from 28.4 ± 5.3% to 34.7 ± 5.9%.…”
Section: Discussionmentioning
confidence: 52%
“…21 However, this new categorization has not been widely evaluated after ACS. [22][23][24] In a single-centre study from Israel, investigators have observed higher mortality among patients with STEMI (n = 2086) undergoing primary percutaneous coronary intervention (PCI) who had mildly reduced EF, as compared with normal EF. 9 Similarly, in another single-centre retrospective cohort study from Northern Ireland (n = 533), mildly reduced EF after STEMI was associated with higher composite outcome of death, hospitalization for HF, or ventricular arrhythmias, compared with patients with normal EF.…”
Section: Discussionmentioning
confidence: 99%